4(4x+1)=3x-4(6-x)8

Simple and best practice solution for 4(4x+1)=3x-4(6-x)8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(4x+1)=3x-4(6-x)8 equation:


Simplifying
4(4x + 1) = 3x + -4(6 + -1x) * 8

Reorder the terms:
4(1 + 4x) = 3x + -4(6 + -1x) * 8
(1 * 4 + 4x * 4) = 3x + -4(6 + -1x) * 8
(4 + 16x) = 3x + -4(6 + -1x) * 8

Reorder the terms for easier multiplication:
4 + 16x = 3x + -4 * 8(6 + -1x)

Multiply -4 * 8
4 + 16x = 3x + -32(6 + -1x)
4 + 16x = 3x + (6 * -32 + -1x * -32)
4 + 16x = 3x + (-192 + 32x)

Reorder the terms:
4 + 16x = -192 + 3x + 32x

Combine like terms: 3x + 32x = 35x
4 + 16x = -192 + 35x

Solving
4 + 16x = -192 + 35x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-35x' to each side of the equation.
4 + 16x + -35x = -192 + 35x + -35x

Combine like terms: 16x + -35x = -19x
4 + -19x = -192 + 35x + -35x

Combine like terms: 35x + -35x = 0
4 + -19x = -192 + 0
4 + -19x = -192

Add '-4' to each side of the equation.
4 + -4 + -19x = -192 + -4

Combine like terms: 4 + -4 = 0
0 + -19x = -192 + -4
-19x = -192 + -4

Combine like terms: -192 + -4 = -196
-19x = -196

Divide each side by '-19'.
x = 10.31578947

Simplifying
x = 10.31578947

See similar equations:

| 2.75(x)=2x-3 | | -7(x-2)=-4 | | 0.86=exp(-6.2831*f) | | 0.86=exp(-2*pi*f) | | (3x-2)2=(2x+3)2 | | 9^4x*27^2-3x=1/9 | | x^5x^7/x^6 | | 5-2q=3Q | | 6(4+2x)-(8x-22)=68 | | X^2+0.2x-0.48=0 | | 3(-6)+2y=6 | | -6(x-2)+4(5n-3)=-36 | | 4(b+1)=-2(b+2) | | 8+x-1/x+4 | | -5-2(-6)=7 | | 49w^2-16w=0 | | 2x+3=-18+x | | 13b-6=3b+4 | | -2(-7k+5)+9=-13 | | 229-4x=32x+17 | | 1/9x^2+2/3x-3=0 | | 6-8x=114-29x | | x/5+x/7=8/7 | | 8(x+2)-2=22-4x-8+12x | | 5x+5=10x-20 | | 9x-5y=18 | | 12r^2=27+27r | | 2x+5=115-10x | | 12+2x=2-4x | | -4(t-1)+9t=8t-8 | | 6c^2+9c/3c | | -5(t-1)+7t=6t-6 |

Equations solver categories